Targeting tumor immunosuppressive microenvironment for pancreatic cancer immunotherapy: Current research and future perspective - Li, Ying; Xiang, Shuai; Pan, Wenjun; Wang, Jing; Zhan, Hanxiang; Liu, Shanglong (Frontiers in Oncology, 2023)
Pancreatic cancer is one of the most malignant tumors with increased incidence rate. The effect of surgery combined with chemoradiotherapy on survival of patients is unsatisfactory. New treatment strategy such as immunotherapy need to be investigated. The accumulation of desmoplastic stroma, infiltration of immunosuppressive cells including myeloid derived suppressor cells (MDSCs), tumor associated macrophages (TAMs), cancer‐associated fibroblasts (CAFs), and regulatory T cells (Tregs), as well as tumor associated cytokine such as TGF-β, IL-10, IL-35, CCL5 and CXCL12 construct an immunosuppressive microenvironment of pancreatic cancer, which presents challenges for immunotherapy. In this review article, we explore the roles and mechanism of immunosuppressive cells and lymphocytes in establishing an immunosuppressive tumor microenvironment in pancreatic cancer. In addition, immunotherapy strategies for pancreatic cancer based on tumor microenvironment including immune checkpoint inhibitors, targeting extracellular matrix (ECM), interfering with stromal cells or cytokines in TME, cancer vaccines and extracellular vesicles (EVs) are also discussed. It is necessary to identify an approach of immunotherapy in combination with other modalities to produce a synergistic effect with increased response rates in pancreatic cancer therapy.